Rhamnogalacturonan I in commercial samples of polygalacturonic acid is a functional driver: A study of isolation, structural elucidation, role in immunostimulation and hydrogel mechanics - Xueting Zhang; Chuying Huo; Pengfei Shan; Niping Chen; Quanwei Zhang; Hauyee Fung; Wenting Zhao; Jing Li; Peili Zhu; Shanlong Tang; Ye Yuan; Lin Sun; et al. (Food Hydrocolloids, 2026)

Multi-model drought index for Pakistan's croplands: A data fusion framework and comparative performance analysis - Akash Hussain; Wenting Han; Muhammad Amjad Saleem; Mubashir Ali Ghaffar; Mohsin Ijaz; Wajahat Waseem; Mahmood Hemat; Atiyyah Rafaqat (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Glassy metal organic frameworks enable rapid LiCl oxidation for high-rate Li-Cl2 batteries - Han Wang; Xinru Wei; Chenyu Ma; Wenting Feng; Zihui Liu; Yiming Sun; Yutong Li; Xinghao Zhang; Debin Kong; Linjie Zhi (Chemical Engineering Journal, 2026)

Hydrological response to glacier peak water in the largest inland river basin of China - Haodong Lyu; Gonghuan Fang; Yaning Chen; Wenting Liang; Lei Wang; Jianmin Qiao; Man Chen; Xiaolong Yan; Ruoyan Li; Shiru Han (Journal of Hydrology, 2026)

A multi-source traceability and assessment framework for comprehensive environmental impacts in national parks: A case of Wuyishan National Park - Ying Han; Wenting Luo; Hu Yu (Journal of Cleaner Production, 2026)

A smartphone-coupled electrochemical biosensor based on DNA tetrahedral scaffolds for simultaneous quantification of AFB1 and OTA - Wenting Li; Yongqiang Shi; Yuanyuan Zhu; Yongjian Yu; Dong Han; Xiaobo Zou; Jiyong Shi (Food Chemistry, 2026)

Characterisation of a novel hydrocolloid from gelatinous Naematelia aurantialba - Wenyuan Li; Wenhuan Xu; Bodun Zhao; Wenting Yang; Bowen Han; Xiaoju Tian; Weigang Chang; Xiaxia Zhang; Xiaobo Dong (Food Hydrocolloids, 2026)

Effects of different water and nitrogen on nitrate distribution and leaching in soil, nitrogen uptake, utilization and translocation by winter wheat - Weina Xu; Baoping Yang; Zhikuan Jia; Wenting Han (European Journal of Agronomy, 2026)

A multi-faceted indirect anticyanobacterial mechanism through cell-free filtrates of Enterobacter cloacae TL3 - Han Yang; Xin Gan; Yaqi Zheng; Tong Liu; Wenting Shen; Erik Jeppesen; Wei Zhang; Liqing Wang (Environmental Research, 2026)

How does peanut yield fluctuate under irrigation practices and precipitation anomalies? Modelling insights from the North China plain - Shah Jahan Leghari; Wenting Han; Ghulam Raza Sargani; Yaseen Laghari; Yichang Wei; Lihua Cui; Abdul Hafeez Laghari; Mukesh Kumar Soothar; Uzair Ahmad; Wajahat Waseem (Agricultural Systems, 2026)

Online trajectory planning method for ascent phase of combined-cycle aerospace vehicle based on segmented hybrid network strategy - Wenjing Han; Yuanwen Cai; Moyao Yu; Wenting Han; Chunmiao Yu; Bingqin Liu (Advances in Space Research, 2026)

Enhancing maize aboveground biomass estimation through time-series UAV-based multispectral and thermal imagery and improved FAO66 model - Guomin Shao; Wenting Han; Huihui Zhang; Beibei Zhou; Yi Wang; Yu Zhang; Li Yuan Zhang; Yaxiao Niu; Quan Xue (International Journal of Remote Sensing, 2026)

Unveiling the causes of winter haze in southern Sichuan via observations and explainable machine learning - Gaofeng Zhou; Junjie Wang; Wenting Lv; Yingjie Li; Yuan Li; Xuefeng Zhang; Li Han; Tao Jiang (Atmospheric Environment, 2026)

Rapid and one-pot detection of nucleic acids within mRNA vaccines based on a dual amplification strategy with PER-CSD - Feifan Yin; Miao He; Han Pan; Murilege Chao; Jinhua Chen; Qiufeng Wang; Wenting Cheng; Zhongyun Wang; Yang Xiang (Analytica Chimica Acta, 2026)

Magnetic separation coupled with gold nanoparticle-assisted hybridization chain reaction for simultaneous detection of exomiR-21 and exomiR-155 - Wenting Cheng; MuRilege Chao; Miao He; Yongliang Cai; Han Pan; Zhongyun Wang; Yang Xiang (Analytica Chimica Acta, 2026)

Impact of reversible and irreversible gas-particle partitioning of atmospheric carbonyl compounds on oxalic acid formation and δ¹ ³C distribution in Northwest China - Weining Qi; Yongming Han; Yali Liu; Yifan Zhang; Wenting Dai; Teng Teng; Minxia Shen; Lu Li; Xiao Guo; Yue Cao; Yingkun Jiang; Qian Wang; et al. (Journal of Hazardous Materials, 2025)

Asymmetrical effects of climatic deterioration versus alleviation on cross-border capital inflows mediated by investor sentiments - Ziwen Cao; Wenting Han (Journal of Environmental Management, 2025)

Development and characterization of Agriophyllum squarrosum starch nanoparticles for enhanced pickering emulsification stability - Lihong Han; Xiaofan Yang; Wenting Fu; Yuanyuan Li; Zhaojun Wei; Donghong Liu; Shuang Qiu (Food Chemistry, 2025)

Soil salinity estimation incorporating environmental covariables using UAV remote sensing for precision field management - Weitong Ma; Wenting Han; Xin Cui; Huihui Zhang; Liyuan Zhang; Yuxin Dong; Xuedong Zhai (Computers and Electronics in Agriculture, 2025)

Efficient surface reaction pathways in metal-free organic semiconductors for practical photocatalytic hydrogen peroxide production - Yujia Li; Jingyi Xu; Siyue Wang; Bing Han; Wenting Li; Xiaolin Zhu; Yongfa Zhu (Science Bulletin, 2025)

Network-based insights into the temperature-driven mechanisms of bacterial self-assembly in the solid-state fermented vinegar seed Pei - Mingchao Jiang; Yiyang Zou; Yuhang Wang; Yunsong Yang; Dong Han; Wenting Li; Yuanyuan Zhu; Yuqin Wang; Zhen Yu; Ke Wang; Chunchi Rong; Peng Liu; et al. (Food Bioscience, 2025)

Physicochemical characteristics and therapeutic mechanisms of Sargassum horneri-derived soluble dietary fiber in cyclophosphamide-induced intestinal damage via gut microbiota and metabolic modulation - Fanghang Li; Jing Tian; Yezhu Xu; Wenting Yi; Qiang Chen; Jiteng Wang; Su Jiang; Yunping Tang; Tao Han (Food Bioscience, 2025)

Seawater intrusion causes substantial release of dissolved organic carbon in coastal paddy soils - Wenting Chi; Yang Yang; Pei Wang; Chao Guo; Zebin Hong; Shiwen Hu; Kuan Cheng; Shan Wang; Han Li; Qi Wang; Ying Li; Yang Wu; et al. (Geochimica et Cosmochimica Acta, 2025)

Insights into the changes in cell wall polysaccharides and ROS metabolism of fresh-cut chili pepper (Capsicum annuum L.) infected by Enterobacter cloacae - Zudi Li; Xiaoyan Zhao; Dan Wang; Pan Wang; Shuang Zhao; Hangjun Chen; Yanchao Han; Wenting Zhao (Postharvest Biology and Technology, 2025)

The suitable spatial resolution of crop type mapping at plot-level in Hetao Irrigation District of China based on UAV remote sensing - Guang Li; Wenting Han; Jiaqi Wei; Mingsheng Shang; Diwen Xiong; Xuedong Zhai; Shenjin Huang; Liyuan Zhang (International Journal of Remote Sensing, 2025)

Does slope cropland to natural and artificial conversion change patterns of soil moisture–carbon trade-offs in time and depth on the water-scarce Loess Plateau, China? - Guowei Nan; Jinghui Wang; Lei Han; Xinyu He; Wenting Jiang; Jifu Ma (Agriculture, Ecosystems & Environment, 2025)

Predicting the adsorption capacity of geopolymers for heavy metals in solution based on machine learning - Yongming Han; Wenting Dai; Lu Zhou; Lisheng Guo; Mo Liu; Dehong Wang; Yanzhong Ju (Journal of Environmental Chemical Engineering, 2025)

Research progress of non-coding RNA regulating the role of PANoptosis in diabetes mellitus and its complications - Guangyu Han; Kaibo Hu; Tianfeng Luo; Wenting Wang; Deju Zhang; Liu Ouyang; Xiao Liu; Jianping Liu; Yuting Wu; Jianqi Liang; Jitao Ling; Yixuan Chen; et al. (Apoptosis, 2025)

Multi-source remote sensing imagery collaboration method based on super-resolution reconstruction - Guang Li; Wenting Han; Jiaqi Wei; Mingsheng Shang; Diwen Xiong; Xuedong Zhai; Yuxin Dong; Liyuan Zhang (International Journal of Remote Sensing, 2025)

UAV multispectral remote sensing for the estimation of SPAD values at various growth stages of maize under different irrigation levels - Weitong Ma; Wenting Han; Huihui Zhang; Xin Cui; Xuedong Zhai; Liyuan Zhang; Guomin Shao; Yaxiao Niu; Shenjin Huang (Computers and Electronics in Agriculture, 2024)

Bioengineering human heavy-chain nanoferritin for glioblastoma multiforme-specific delivery and efficient immunotherapy - Han Yan; Wenting Cheng; Siyuan Qin; Jing Zuo; Lei Li; Jing Zhang; Qinxia Chang; Yonghao Yan; Shiqi Wang; Canhua Huang; Haiyuan Zhang (Chemical Engineering Journal, 2024)

Using SAR imagery to extract flash flood sediment deposition area in the northern Loess Plateau - Xiaowu Ma; Juying Jiao; Bo Yang; Wenting Zhao; Qi Ling; Xinhan Zhang; Jianqiao Han; Pengfei Du; Yin Chen; Hao Chen (Journal of Hydrology, 2024)

What should we do for water security? A technical review on more yield per water drop - Shah Jahan Leghari; Wenting Han; Kelin Hu; Yaseen Laghari; Yichang Wei; Lihua Cui (Journal of Environmental Management, 2024)

Effects of neonicotinoid residues on non-target soil animals: A case study of meta-analysis - Yuxuan Cao; Wenting Zhao; Jinrui Zhang; Daniel M. Figueiredo; Mingyu Zhao; Siyang Ren; Hongyu Mu; Yiyi Li; Huan Lu; Haoyuan Shi; Xin Li; Jindong Li; et al. (Journal of Hazardous Materials, 2024)

Modal shift, environmental benefits and population exposure assessment on contingent transport policies - Ke Han; Yueqi Liu; Wenting Zhong (Transportation Research Part D: Transport and Environment, 2024)

Impact of ocean acidification on microzooplankton grazing dynamics - Wenting Shi; Xiaoting Fu; Yabo Han; Jiahui Qin; Jun Sun (Frontiers in Marine Science, 2024)
This study examines the potential impacts of projected atmospheric carbon dioxide ( p CO 2 ) levels reaching 800 ppm by the end of the century, focusing on ocean acidification effects on marine ecosystems in the coastal areas of Bohai. We investigated how acidification affects the grazing patterns of microzooplankton using dilution techniques and ecophysiological methods. Our findings indicate that acidic conditions shift the phytoplankton community structure, changing dominant species. Elevated CO 2 concentrations reduced grazing pressure on phytoplankton, with less steep declines in growth rates at 800 ppm CO 2 (spring: 2.43 d −1 vs. 2.16 d −1 , summer: −0.46 d −1 vs. −0.73 d −1 , autumn: −0.45 d −1 vs. −0.90 d −1 ) and significant decreases in grazing pressure percentages (%Pp from 0.84 to 0.58 and %Pi from 0.64 to 0.46). Short-term acid exposure significantly increased superoxide dismutase activity in both microplankton (from 0.03 to 0.08 U mg −1 , p<0.01) and nanoplankton (from 0.05 to 0.09 U mg −1 , p<0.001), indicating an adaptive response to oxidative stress. These results highlight that elevated CO 2 levels primarily boost phytoplankton growth by reducing microzooplankton grazing pressure, resulting in higher growth rates and a shift towards smaller-sized phytoplankton, reflecting complex short-term ecological responses to acidification. Further research is needed to understand the long-term effects of ocean acidification on microzooplankton and their role in marine secondary productivity.

Lignin's complex role in lignocellulosic biomass Recalcitrance: A case study on bamboo - Wenting Ren; Dongsheng Zhang; Yan Zhou; Han Wang; Linmin Xia; Chenshu Tan; Fei Guo; Xuexia Zhang; Rilong Yang; Yan Yu (Chemical Engineering Journal, 2024)

Estimating maize plant height using a crop surface model constructed from UAV RGB images - Yaxiao Niu; Wenting Han; Huihui Zhang; Liyuan Zhang; Haipeng Chen (Biosystems Engineering, 2024)

Long-term use of etomidate disrupts the intestinal homeostasis and nervous system in mice - Siming Ding; Kan Li; Xing Han; Wenting Lin; Yingjun Qin; Renjuan Cao; Yuan Ren (Toxicology, 2024)

Neurotoxic effects induced by flunitrazepam and its metabolites in zebrafish: Oxidative stress, apoptosis, and histone hypoacetylation - Yingjun Qin; Yajing Huang; Wenting Lin; Rui Huang; Kan Li; Xing Han; Yuan Ren (Science of The Total Environment, 2024)

Lignocellulosic fraction-induced niche differentiation within dissimilatory iron reducing bacterial groups in a paddy soil - Yunbin Jiang; Wenting Hu; Kailou Liu; Shangshu Huang; Fengwu Zhou; Cheng Han; Huan Deng; Wenhui Zhong (Soil Ecology Letters, 2024)

Flunitrazepam induces neurotoxicity in zebrafish through microbiota-gut-brain axis - Wenting Lin; Kan Li; Yingjun Qin; Xing Han; Xiaohui Chen; Yuan Ren (Science of The Total Environment, 2023)

Distribution and formation of soil balls under heavy rainstorm conditions in the northern Loess Plateau - Bo Yang; Juying Jiao; Xiaowu Ma; Wenting Zhao; Qi Ling; Xinhan Zhang; Jianqiao Han; Pengfei Du; Yin Chen; Hao Chen (Journal of Hydrology, 2023)

Cost-efficient bathymetric mapping method based on massive active–passive remote sensing data - Tong Han; Huaguo Zhang; Wenting Cao; Chengfeng Le; Chen Wang; Xinke Yang; Yunhan Ma; Dongling Li; Juan Wang; Xiulin Lou (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Seed Endophytes and Their Roles in Host Plant Stress Resistance - Wenqin Mao; Yuanshuang Wu; Fang Li; Wenting Tang; Weijun Gong; Xue Han; James F. White; Xiuling Ji; Haiyan Li (Journal of Soil Science and Plant Nutrition, 2023)

Efficient photoelectrochemical aptasensing of di-2-ethylhexyl phthalate in environmental samples based on N, S co-doped graphene quantum dots/TiO2 nanorods - Dongyun Liao; Jinfeng Zhi; Qiang Wang; Wenjun Yan; Yujing Guo; Yujie Han; Chuan Dong; Yong Xiao; Hongcun Bai; Wenting Liang; Lifang Fan (Analytica Chimica Acta, 2023)

Green and cost-efficient functionalized clay adsorbent enables one-step ultraefficient removal of Pb(II) at very low and high concentrations - Huan Zhang; Xin Fan; Xiangyu Liu; Qingdong He; Wenting Zhao; Lei Han; Jingjing Cui; Fang Guo; Wenbo Wang (Applied Clay Science, 2023)

Sustainable green conversion of coal gangue waste into cost-effective porous multimetallic silicate adsorbent enables superefficient removal of Cd(II) and dye - Wenting Zhao; Ke Feng; Huan Zhang; Lei Han; Qingdong He; Fei Huang; Wenmeng Yu; Fang Guo; Wenbo Wang (Chemosphere, 2023)

Identification and genetic analysis of major gene ST3GAL4 related to serum alkaline phosphatase in chicken - Hehe Tang; Yanchao Ma; Jianzeng Li; Zhenzhen Zhang; Wenting Li; Chunxia Cai; Lujie Zhang; Zhuanjian Li; Yadong Tian; Yanhua Zhang; Jinqing Ji; Lu Han; et al. (Research in Veterinary Science, 2023)

Evaluating soil moisture content under maize coverage using UAV multimodal data by machine learning algorithms - Yu Zhang; Wenting Han; Huihui Zhang; Xiaotao Niu; Guomin Shao (Journal of Hydrology, 2023)

Comprehensive study of thermal degradation behavior of carbon fiber flexible sucker rods: Product characteristics, kinetics and thermodynamics - Wenhan Guan; Zhaohui Han; Wenting Su; Shenghui Guo; Yongjing Guo (Fuel, 2023)

Biomarker selection strategies based on compound stability in wastewater-based epidemiology - Zhihan Gao; Ping Li; Han Lin; Wenting Lin; Yuan Ren (Environmental Science and Pollution Research, 2023)

Ultraviolet photolysis of four typical cardiovascular drugs: mechanisms, influencing factors, degradation pathways, and toxicity trends - Senwen Ping; Wenting Lin; Anchen Liu; Zhihan Gao; Han Lin; Yuan Ren (Environmental Science and Pollution Research, 2021)

Ferroptosis is involved in the development of neuropathic pain and allodynia - Huixing Wang; Xiaodong Huo; Chenyang Han; Jiang Ning; Hongguang Chen; Bo Li; Jingzhi Liu; Wenting Ma; Quanbo Li; Yonghao Yu; Kemei Shi (Molecular and Cellular Biochemistry, 2021)

Carbon content in airway macrophages and genomic instability in Chinese carbon black packers - Wenting Cheng; Yuansheng Liu; Jinglong Tang; Huawei Duan; Xiaoran Wei; Xiao Zhang; Shanfa Yu; Matthew J. Campen; Wei Han; Nathaniel Rothman; Steven A. Belinsky; Qing Lan; et al. (Archives of Toxicology, 2020)

Increased drought and atmospheric CO2 positively impact intrinsic water use efficiency but do not promote tree growth in semi-arid areas of northwestern China - Kanglong Lu; Ning Chen; Xiaowei Zhang; Jingru Wang; Minghao Wang; Salman Khan; Chun Han; Cankun Zhang; Shuyuan Wang; Luning Wang; Wenting Gao; Yongjing Liu; et al. (Trees, 2019)

Characteristics of single atmospheric particles in a heavily polluted urban area of China: size distributions and mixing states - Li Li; Qiyuan Wang; Xu Zhang; Yuanyuan She; Jiamao Zhou; Yang Chen; Ping Wang; Suixin Liu; Ting Zhang; Wenting Dai; Yongming Han; Junji Cao (Environmental Science and Pollution Research, 2019)

Path Loss Estimation for Wireless Underground Sensor Network in Agricultural Application - Xiaoqing Yu; Wenting Han; Zenglin Zhang (Agricultural Research, 2017)

Modeling urban growth by the use of a multiobjective optimization approach: Environmental and economic issues for the Yangtze watershed, China - Wenting Zhang; Haijun Wang; Fengxiang Han; Juan Gao; Thuminh Nguyen; Yarong Chen; Bo Huang; F. Benjamin Zhan; Lequn Zhou; Song Hong (Environmental Science and Pollution Research, 2014)